Digital Walls or Digital Bridges? Telehealth for Mental Health Equity Among Palestinians in the West Bank and Gaza - Ibrahim Aqtam (Journal of the American Psychiatric Nurses Association, 2026)
Objective: The expansion of telehealth in mental health nursing raises questions about reducing or exacerbating health inequities. For Palestinians living in the West Bank and Gaza facing movement restrictions, infrastructure fragmentation, and chronic trauma, this question is pressing. This conceptual discussion paper critically examines whether telehealth is a “digital wall” reinforcing barriers or a “digital bridge” expanding equitable access. Methods: This paper synthesizes peer-reviewed literature and United Nations reports. Literature was purposively selected based on conceptual relevance to digital equity, conflict-affected settings, and psychiatric mental health (PMH) nursing, including literature specifically addressing the role of PMH nurses (PMHNs) in conflict zones. The Digital Health Equity Framework guides the thematic analysis organized around infrastructure, affordability, privacy, cultural appropriateness, and community resilience. This is not a systematic review. Results: Available evidence suggests telehealth may function as a barrier or facilitator depending on context. Infrastructure, economic, privacy, and cultural barriers risk making telehealth exclusionary. Conversely, telehealth may bridge access by reducing travel through checkpoints and enabling continuity during military escalations. The critical and underrecognized barrier of inadequate training in telemedicine practice threatens adoption across all provider levels in Palestine. PMHNs occupy a critical mediating role. Conclusions: Telehealth is neither inherently equitable nor inequitable. PMHNs should assess digital access as a social determinant, offer low-bandwidth alternatives, and advocate for structural investments. Capacity building to address the training gap is essential for telehealth integration. Telehealth equity in conflict-affected settings depends less on technology than on whether systems are designed around patients’ actual conditions and community resilience.